2016
DOI: 10.1007/s41105-016-0067-5
|View full text |Cite
|
Sign up to set email alerts
|

Day workers suffering from a wider range of sleep problems are more likely to experience suicidality

Abstract: Both a higher suicide rate and widespread sleep problems are serious health concerns in Japan when compared with those of other countries. We investigated the relationship between suicidal ideation and sleep problems in Japanese day workers using the 3-dimensional sleep scale (3DSS), which measures three sleep elements (phase, quality, and quantity). Data from 635 Japanese day workers (461 mens and 174 womens) were included. The 3DSS was used to assess participants' sleep condition. Participants were classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…This suggests that it is necessary to assess sleep phase, quality, and quantity separately to clarify the causes of sleep complaints and respond appropriately. Compared to a previous study [ 20 ], the prevalence of poor sleep phase in this study was lower while that of poor sleep quality or quantity were similar. Specifically, the previous study reported that the prevalence of poor sleep phase was about 44%, whereas in this study, it was 37%.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…This suggests that it is necessary to assess sleep phase, quality, and quantity separately to clarify the causes of sleep complaints and respond appropriately. Compared to a previous study [ 20 ], the prevalence of poor sleep phase in this study was lower while that of poor sleep quality or quantity were similar. Specifically, the previous study reported that the prevalence of poor sleep phase was about 44%, whereas in this study, it was 37%.…”
Section: Discussioncontrasting
confidence: 91%
“…In the past, we established that sleep comprises three measurable elements—phase, quality, and quantity—which we then integrated into an original scale called the 3-Dimensional Sleep Scale (3DSS) [ 19 , 20 ]. In our current 24-h society, people often exhibit problems in their sleep phase (e.g., regularity and chronotype), as well as in their sleep quality (e.g., sleep efficiency and satisfaction) and quantity (e.g., sleep duration and fullness).…”
Section: Introductionmentioning
confidence: 99%
“…At this point, we can make the argument that sleep disturbances may be a marker of distress and suicide risk 127 and that multiple concurrent sleep problems may confer greater risk for suicide than single sleep problems. 66 , 141 Mechanisms explaining the relation between sleep disorders and suicide remain needed, including more research rigorously examining the efficacy of sleep-disorder treatments on assuaging suicide risk. Research examining the impact of sleep disorders on suicide risk has been circumscribed to a few sleep-disorder symptoms, with much less known about the prevalence and management of suicide risk across all sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Research focusing on chronotypes have shown associations between an “eveningness” preference and suicide-related thoughts 141 144 and behaviors (ie, lifetime and violent suicide attempts). 145 , 146 An eveningness preference has also been associated with elevated scores on measures of depressive symptoms, hopelessness, and defeat.…”
Section: Circadian Rhythm Sleep–wake Disordersmentioning
confidence: 99%
See 1 more Smart Citation